"Enjoy!" The Effects of Service Blessings on the Customer. Issue 1 (2nd January 2022) - Schindler, Robert M.; Sen, Sandipan S.; Wiles, Judy A.
ABSTRACT: In religious traditions, emphatic utterances that activate good feelings are referred to as blessings . Interviews with a wide variety of service providers indicate that they routinely use such utterances regarding the choices and prospective choices of their customers. Further, such service blessings typically show characteristics that are consistent with both religious traditions and rituals of everyday politeness. A controlled experiment indicates that service blessings can have substantial and broad benefits to customer satisfaction. These findings have both theoretical and practical implications for improving the management of retail customer service.